Intrinsic Charge Trapping and Reversible Charge Induced Structural Modifications in a‐Si3N4 - Lukas Hückmann; Jonathon Cottom; Jörg Meyer (Advanced Physics Research, 2024)
Abstract Amorphous silicon nitride (a‐Si3N4) is an essential material for a wide variety of electronic devices, ranging from its use in dielectric layers to its paramount importance for memory applications. In particular, the latter has triggered the interest in charge trapping, for which so‐called N‐ and K‐centers have been identified in experiments – with the atomistic configuration still subject of vigorous debate. Here, the range of hole and electron traps in stoichiometric a‐Si3N4 are revealed by combining atomistic calculations at different levels of theory. The variety of sites within the amorphous network are characterized by introducing a statistical sampling method to quantify the statistical completeness of structural models obtained from a melt‐quench procedure, in combination with a powerful local descriptor inspired by Tolman's angle. Hole trapping is dominated by two‐coordinate N‐centers, resulting in shallow hole traps. In contrast, electron trapping exhibits more nuanced behavior, encompassing both intrinsic polaronic trapping and the previously identified K‐center type trapping (silicon dangling bond *SiN3). Intrinsic polaronic trapping originates from distorted SiN4 tetrahedra. Structural relaxation of the intrinsic polaron sites results in significant elongation of a Si‐N bond and reversible generation of *SiN3 and N3Si‐SiNx ∈ {3, 4} defects.